1968
DOI: 10.1007/bf00188941
|View full text |Cite
|
Sign up to set email alerts
|

The critical tensile stress criterion for cleavage

Abstract: An elastic-plastic analysis was used to accuratel~¢ measure the microscopic cleavage strength o~of notched bars of high nitrogen steel in bending. It was found that o~f increases as the root radius of the notch/9 decreases. For/9 > 0.010", the variation of o~f with p, and the difference between 0~f and the cleavage fracture strength of a plane tensile specimen, of, may result from a statistical effect, due to differences in the volume of highly stressed material in the plastic zone• For/9 < .010", the primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1970
1970
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…Furthermore, they advocated that a necessary condition for fracture was that the local flow stress within the crack tip enclave must exceed some critical value before secondary cracks can be initiated. Basically, this model implies some critical distance concept, called L Ã , which is similar to that employed by other reseasrchers [24,25] and this is illustrated schematically in Fig. 8.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, they advocated that a necessary condition for fracture was that the local flow stress within the crack tip enclave must exceed some critical value before secondary cracks can be initiated. Basically, this model implies some critical distance concept, called L Ã , which is similar to that employed by other reseasrchers [24,25] and this is illustrated schematically in Fig. 8.…”
Section: Discussionmentioning
confidence: 98%
“…In two-dimensional (2D) analyses, Hill (1949) derived an upper-bound solution for the notched ideal plastic-rigid material. Hill's main conclusion shows that the limit load increases with the decreasing flank angle of the notch (Tetelman et al, 1968), and attains its maximum value when the notch angle turns to 01 (a sharp edge-crack). Considering the notches are deep enough that the plasticity is confined in the ligament, Rice et al (1973) developed the J-integral formula for the double-edge-notched plate in tension.…”
Section: Introductionmentioning
confidence: 93%
“…4.3 Effect of notch geometry on the local cleavage fracture stress Tetelman et al (1968) investigated the effect of notch root radius on the local cleavage fracture stress σ f by means of slip-line field analysis. They suggested that when the root radius was larger than 0.254 mm, σ f may vary with root radius, because of differences in stressed volumes.…”
Section: Effect Of Loading Rate On the Local Cleavage Fracture Stressmentioning
confidence: 99%
“…It is well known that the cleavage fracture of ferrite steels is controlled by a critical local tensile stress criterion (σ yy ≥ σ f ) (Knott 1966;Tetelman et al 1968;Ritchie et al 1973; Thompson and Knott 1993). A salient feature of cleavage fracture is the variability of experimental results.…”
Section: Introductionmentioning
confidence: 99%